Pengaruh Intensitas Modal, Leverage dan Komisaris Independen terhadap Agresivitas Pajak - Emelia Elisa Stefanny; Dedi Haryadi (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to determine the effect of capital intensity, leverage, and independent commissioners on tax aggressiveness as measured by the Effective Tax Rate (ETR). The population of this study consists of 132 companies in the consumer non-cyclical sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. A total of 45 companies were obtained as samples using the purposive sampling method. The secondary data used in this study are annual financial statements obtained from the official IDX website at www.idx.co.id/id. The data analysis techniques employed include descriptive statistical tests, panel data regression analysis consisting of the Chow test, Hausman test, and Lagrange Multiplier test, as well as the coefficient of determination (R²) test, F-test, and t-test, using EViews 12 software. The model feasibility test results indicate that the Random Effect Model (REM) is appropriate for this study. The results of the panel data regression analysis, along with the coefficient of determination, F-test, and t-test, show that the probability value of the capital intensity variable is 0.6920 > 0.05 and that of independent commissioners is 0.0010 < 0.05, indicating no significant effect on tax aggressiveness, while the leverage variable with a probability value of 0.8792 > 0.05 has a significant effect on tax aggressiveness.